Determinants of the performance of gulf commercial bank using the camel model - Aqeel Shakir Abd, Salim Sallal Rahi,; Shareeef AL-Morshedi, Abbas Alwan (Opción, 2019)
The research aimed to analyze the performance by using elements of the CAMEL model, and identify factors that are most impacting on performance via the application of the CAMEL model to the Gulf Commercial Bank. The study found that when looking at all the capital adequacy ratios of the bank and for all years of study, it is much higher than the capital adequacy indicators approved by the Basel Committee. In conclusion, although asset quality ratios vary for years of schooling, they remain a very acceptable proportion.